Glove Perforation In Orthopedic Trauma Surgery (Journal of Pakistan Orthopaedic Association, 2014)
Objective: To evaluate the frequency of glove perforation during the lower limb fracture fixation procedures.Material and methods: This prospective study was conducted at orthopedic and spine surgery unit Hayatabad medical complex Peshawar from may 2014 to November 2014. Data was collected from a total of 85 lower limb fracture fixation surgeries. A total of 85 surgeons, 85 first assistants and 85 scrub assistants were included in the study. Double gloves were used by all of them. Gloves were changed for perforation during surgery or due to excessive soakage or contamination. Gloves used in all surgeries were from the same company.Results: In total 85 operations operative perforation rate was 49% (42/85) and the overall glove perforation rate was 16% (193/1195). Of 193 perforated gloves outer gloves were perforated 85 %( 164/193) and inner 15 %( 29/193). Out of 29 inner gloves perforation 22 inner gloves perforation accompanied outer gloves perforations at the same site and only on 7 occasions’ inner gloves were perforated without outer glove perforation. Only 24 %( 46/193) of the perforated gloves were identified during surgery and 76 %( 147/193) of the perforations were detected by water loading test. Of 85 total operations 17 were emergency surgeries while 68 were elective surgeries. Operative perforation rate was 70 %( 12/17) and glove perforation rate was 27 %( 59/219) in emergency surgeries, which is significantly more than elective procedures. Among the elective surgeries the highest glove perforation was noticed for Ilizarov procedure, operative perforation rate was 90 %( 8/9) and glove perforation rate was 40 %( 53/134). Left hand was involved in 75% perforations. Commonly perforated site was left index finger (36%) followed by left thumb (31%).Conclusion: The incidence of glove perforation is high in orthopedic trauma procedures. Double gloving can provide better protection for surgical team as well as patient.Keywords: Double gloves, perforation, infection, orthopedic surgery.